Elastocapillary thinning dynamics in ferroelectric nematic filaments - Bidisha Bag; K. Anaswara Das; Anirban Debnath; Tejasvi Hegde; Harish N. Dixit; Jakub Karcz; Przemysław Kula; Surajit Dhara (Proceedings of the National Academy of Sciences, 2026)
Ferroelectric nematic liquid crystals (FNLCs) represent an emerging class of functional soft materials that combine the orientational order of nematic liquid crystals with spontaneous electrical polarization. In a striking departure from the conventional nonpolar nematic liquid crystals, FNLCs form freely suspended liquid filaments that thin in time. These filaments exhibit a two-stage thinning dynamics, consisting of an initial elastocapillary regime followed by a terminal visco-elastocapillary regime before rupture. Videomicroscopy and rheological measurements show that the FNLC studied in this work behave as an elastic liquid with a high extensional relaxation time, closely analogous to Boger fluids—a well-known class of elastic liquids composed of very dilute solutions of flexible polymer and viscous solvent. Our findings point to a substantial contribution of long-range polar order to the mechanical response of ferroelectric nematic phases. The thinning dynamics of FNLC filaments thus reveal distinctive mechanical behavior providing fundamental insights into the mechanics of polar nematic phases and offering unique opportunities for electrically tunable control of flow and morphology over extended timescales.